Seasonal distribution of dissolved copper(II) ions at tropical coastal water: in case of Pulau Perhentian, Terengganu - Mohamed, Khairul Nizam; Godon, Edrianna (David Publishing Company, 2020)
Seawater samples from Pulau Perhentian, Terengganu were analysed for Cu(II) speciation concentration. Samples were collected during pre- and post-monsoon seasons, in order to measure the concentration of dCu (dissolved Cu) and CuL (Natural Organic Cu(II) Binding Ligands) by using CLE-AdCSV (Competitive Ligand Exchange-Adsorptive Cathodic Stripping Voltammetry). High [dCu] and [CuL] were determined during pre-monsoon seasons due to a long NEM (Northeast Monsoon) period along with a strong El Niño phenomenon. Water mixing during this period was suggested to be responsible for an input of Cu from bottom sediment into the water column. The Cu(II) speciation analysis has identified the presence of strong class ligands (L1), and it controls the distribution of free Cu2+ ions. Therefore, the presence of Cu2+ ions is below the toxicant level and it functions more towards the bioavailability for microorganisms. Furthermore, there is no significant effect between pre- and post-monsoon season on the dissolved Cu(II)-speciation in the study area, except an influence from the El Niño phenomenon which is unclear as of yet.